Fitness Level Survey Of Futsal Referees In Medan City And Deli Serdang Regency 2025 - Dicky Hendrawan; Eka Abdurrahman; Handi El Fonahia Telaumbanua; Ebit One Nitema Laowo; Muhammad Fadhel Syahputra, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Objectives. The purpose of this study is to determine the fitness level of futsal referees in Medan City and Deli Serdang Regency in 2025 using quantitative methods and data collection techniques using a survey method on the physical fitness conditions of futsal referees in Medan City and Deli Serdang Regency in 2025.Materials and Methods. The survey method is used to obtain data from specific, natural (not artificial) locations. However, this study conducted data collection, for example, distributing questionnaires, conducting tests, and conducting structured interviews (the treatment is not the same as an experiment). This study was conducted to review the physical fitness of futsal referees in Medan City and Deli Serdang Regency in 2025.Results. The analysis results show that 2 referees (6.7%) had cardiorespiratory fitness levels classified as very poor, 3 (10%), 16 (53.3%), 3 (10%), and 6 (20%) were classified as very good.Conclusions. From the data above, it can be concluded that the fitness level of referees in Medan City and Deli Serdang Regency will be in the fairly good category in 2025.